A Review of Modern Surgical Hair Restoration Techniques - Shiell, Richard C (Medknow Publications, 2008)
The field of hair restoration has had a chequered history. From the days of punch grafting to the present day techniques of follicular unit hair transplantation, the field has seen a number of new advances. This article reviews these developments.